2019
DOI: 10.1055/a-0947-5712
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Potential of Ginkgo biloba in Retinal Diseases

Abstract: Like other tissues of the central nervous system, the retina is susceptible to damage by oxidative processes that result in several neurodegenerative disease such as age-related macular degeneration, diabetic retinopathy, glaucoma, ischaemic retinal disease, retinal disease produced by light oxidation, and detached retina, among other diseases. The use of antioxidant substances is a solution to some health problems caused by oxidative stress, because they regulate redox homeostasis and reduce oxidative stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 124 publications
0
31
0
1
Order By: Relevance
“…The leaves and seeds of this plant have been used for medicinal purposes in China for centuries, initially being used for asthma and problems in the digestive system. In Europe and the USA, they have been sold since the sixties, and now they represent one of the most popular phytotherapeutic products in the world [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves and seeds of this plant have been used for medicinal purposes in China for centuries, initially being used for asthma and problems in the digestive system. In Europe and the USA, they have been sold since the sixties, and now they represent one of the most popular phytotherapeutic products in the world [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It could play an antioxidant activity by scavenging free radicals, superoxide anions, and NO, as well as inhibit free radical reaction and lipid peroxidation [ 16 , 17 ]. Martínez-Solís et al [ 18 ] found that flavonoids and terpenoids in ginkgo leaf extracts could be used to prevent and treat retinal diseases related to oxidative stress. Liu et al [ 19 ] found the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px) could be improved by ginkgolide while the concentration of malondialdehyde (MDA) in the myocardial tissue of myocardial ischemia-reperfusion (MI/R) rats.…”
Section: Biological Activity Of Ginkgo Bilobamentioning
confidence: 99%
“…Currently, Ginkgo biloba is an adaptive species and grows well in most parts of the world, including in the Mediterranean climate. The extract of Ginkgo biloba and/or its ginkgolide components, e.g., EGb761, BN52021, BN5739 and BN52063, possess many beneficial effects on the function of several injured and diseased cells and organs, including the nervous [116][117][118][119][120], renal [121][122][123] and cardiovascular [124][125][126][127][128][129][130] systems.…”
Section: Ginkgo Biloba "Ginkgoflavonoids" and Ho-1mentioning
confidence: 99%